Arctic Monitoring and Assessment Programme (AMAP) - Progress Report - Arctic Monitoring and Assessment Programme (AMAP) (Arctic Council Secretariat, 2017)
Summary of AMAP's achivements under the U.S. Chairmanship, 2015-17. Summary of AMAP's achivements under the U.S. Chairmanship, 2015-17.